Pengaruh Tabungan Mudharabah, Deposito Mudharabah Dan Pembiayaan Mudharabah Terhadap Peningkatan Laba Bank - Mhd. Aria Agung Widodo; Tursina Juliani Dalimunthe; Chairina (CV. ULIL ALBAB CORP, 2022)
This study aims to determine the effect of mudharabah deposits and mudharabah savings both partially and simultaneously on the profitability of banks in Indonesia. The data used in this study are data collected from annual reports published by banks in Indonesia that are registered in 2022. The analytical technique used in this study is multiple linear regression analysis. The results of data analysis show that mudharabah deposits have a partial positive and significant effect on profitability, mudharabah savings have a partial positive effect but not significant. Mudharabah deposits and mudharabah savings simultaneously affect profitability.